RELEVANSI PEMIKIRAN KUNTOWIJOYO TENTANG SAINTIFIKASI ISLAM - SURIP SURIP (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2022)
By using descriptive qualitative research method through a literacy study approach. The problem-solving procedure is carried out based on problems that arise with the study of literature in the main book of Islam from Kuntowijoyo Science with Islamic scientific thinking. , the verse of the universe (kosmos) and the verse of self or history, the verse of the universe and the verse of self are contained in Surah al-Fushilat: 53 with the understanding that the three verses are manifestations of God's truth for people who always think. With Islamic Studies the dichotomy of religious and general knowledge is no longer valid, the application of knowledge taught in Islamic educational institutions is already Islamic. Social sciences, exact sciences (exact), tool science and religious science all lead to the verses of Allah conveyed through the Qur'an to humans, with Islamic scientific thinking, the interdisciplinary knowledge taught in Islamic educational institutions is part of the religious disciplines, so that students who study at Islamic boarding schools, Madrasas, and diniyyah are no longer exclusive about science, both are part of science that must be sought anytime and anywhere based on faith. ABSTRAKDengan menggunakan penelitian Metode kualitatif deskriftif melalui pendekatan studi literasi. Prosedur pemecahan masalah dilakukan berdasarkan permasalahan yang timbul dengan kajian literatur dalam buku utama Islam sebagai Ilmu Kuntowijoyo dengan pemikiran Saintifikasi Islam. Seluruh disiplin ilmu merupakan bagian dari ayat Tuhan, ayat Tuhan terdiri dari dogma Islam yang harus selalu dibaca (Al-Qur'an), ayat Alam semesta (kosmos) dan Ayat diri atau sejarah, ayat alam semesta dan ayat diri terdapat pada surat al-fushilat: 53 dengan pengertian bahwa ketiga ayat itu merupakan manifestasi kebenaran Allah bagi orang yang selalu berfikir. Dengan Pengilmuan Islam dikotomi ilmu pengetahuan agama dan umum tidak berlaku lagi, aplikasi ilmu yang diajarkan di lembaga pendidikan islam sudah bersifat islami. Ilmu sosial, ilmu pasti (exact), ilmu alat dan ilmu agama semua bermuara pada ayat Allah yang di sampaikan melalui al-qur'an kepada manusia, dengan pemikiran pengilmuan Islam maka interdisiplin ilmu yang diajarkan di lembaga pendidikan Islam itu bagian dari disiplin ilmu agama, sehingga santri yang belajar di pondok pesantren, Madrasah, diniyyah sudah tidak lagi ekslusif tentang keilmuan, keduanya merupakan bagian dari ilmu pengetahuan yang harus dicari kapanpun dan dimanapun dengan didasari iman.